A comprehensive study of immune function and immunophenotyping of white blood cells from β-thalassaemia/HbE patients on hydroxyurea supports the safety of the drug - Siriworadetkun S. (2023)
Hydroxyurea (HU) (hydroxycarbamide) is used as a therapeutic option in β-thalassaemia to increase fetal haemoglobin, which results in a reduced requirement for blood transfusion. However, a potential serious adverse effect of HU is neutropenia. Abnormal neutrophil maturation and function in β-thalassaemia/HbE patients are well documented. This raises questions about the effect of the drug with regards to the immune response these patients. This study investigated the effects of HU treatment on both innate and adaptive immunity in a cross-sectional study of 28 β-thalassaemia/HbE patients who had received HU treatment (BE+HU) as compared with 22 β-thalassaemia/HbE patients who had not received HU (BE-HU) and 26 normal subjects. The expression of PU.1 and C/EBPβ, transcription factors, which are associated with neutrophil maturation, was significantly reduced in BE+HU patients as compared with BE-HU patients and normal subjects. Interestingly, C3bR expression on neutrophils and their oxidative burst activity in BE+HU were restored to close to normal levels when compared with BE-HU. There was no observed effect of HU on monocytes, myeloid derived suppressor cells (both granulocytic and monocytic subsets), CD4+T cells, CD8+T cells, complement levels and serum immunoglobulin levels in this study. The full immunophenotyping analysis in this study indicates that HU therapy in β-thalassaemia/HbE patients does not significantly compromise the immune response.